A Soda-Anthraquinone Pulping Of Acacia Mangium - Ibrahim, Rushdan (1990)
T he ob jective of this p roject was to d etermine the eff ect of f our d ifferen t; levels (0.125% , 0 .2 5% , 0 .5% and 1 .0 % ) of anthraquin one(AQ) add itive to s oda pulp ing of n in e- year old Acacia man qium willd. grown in P ahang, Malays ia. S od a-AQ p Ulp ing gave high s creened yields rangin g f rom 47.4% to 51.5% f or the 0 . 125% AQ and 1 .0% AQ add ition respectively. B leachab ility, as indicated by the d ecreas ing Kapp a numb er ( 2 6 . 3 to 2 3 . 2 ) , was improved with increas ing add ition of AQ. Excep t f or f olding enduran ce, the s trength p roperties of the s od a-AQ pulps were als o improved and higher than b oth s oda and kraft Acacia manqiu m pulps .